Functionally graded viscoelastic core characteristics on vibroacoustic behavior of double-walled cylindrical shells in a subsonic external flow. (January 2023) - Reaei, Shohreh; Talebitooti, Roohollah
The present study is concerned with an analytical solution for calculating sound transmission loss through an infinite double-walled circular cylindrical shell with two isotropic skins and a polymeric foam core. Accordingly, the two-walled cylindrical shell is stimulated applying an acoustic oblique plane wave. The equations of motion are derived according to Hamilton's principle using the first-order shear deformation theory for every three layers of the construction. Additionally, by the aid of employing the Zener mathematical model for the core of polymeric foam, mechanical properties are determined. To authenticate the results of this study, the damping of the core layer goes to zero. Therefore, the numerical results in this special case are compared with those of isotropic shells. The results prove that the presented model has high accuracy. It is also designated that decreasing the power-law exponent of the core leads to improving the sound transmission loss through the thickness of the construction. Besides, in addition to probe some configurations versus alterations of frequencies and dimensions, the convergence algorithm is provided. Consequently, it is realized that by increasing the excitation frequency, the minimum number of modes to find the convergence conditions is enhanced. The results also contain a comparison between the sound transmission loss coefficient for four different models of a core of a sandwiched cylindrical shell. It is comprehended that the presented model has a transmission loss coefficient more than the other types of the core at high frequencies.